(untitled) (Research, Society and Development, 2022)
Introduction: The dissemination of information about the risks of consuming ultra-processed foods and also about healthier options, such as fortified foods, has grown among the general population. The flour obtained from mesquite proves to be a viable alternative to be used in bakery foods. Objective: To analyze the nutritional composition of mesquite pod flour, developing breads with the aforementioned product and observing its acceptance by potential consumers. Methodology: The flour was obtained through a drying and grinding process, followed by the analysis of macronutrients, moisture, crude fiber, ash, calcium and iron. Results: The physicochemical results stood out for proteins 8,85%, crude fiber 12,65%, lipids 0,31%, calcium 182,0 mg/100g and iron 6,0 mg/100g. In addition to expressive results compared to other flours for total phenolics, total flavonoids and tannins, with 11,73; 1,76 and 4,83 mg/g, respectively. The sensory analysis showed that the bread formulations with the new flour did not show a significant difference between the attributes compared to the standard. Regarding the components, ash and calcium also showed a significant difference in these two samples. In this way, it is concluded that values of fiber, minerals and phenolic compounds in flour are attractive for the control of intestinal health, combating free radicals and adequate intake of micronutrients, according to the literature. Conclusion: The preparation of bread formulations using this flour was accepted by potential consumers, as well as traditional wheat flour breads are accepted. Therefore, it is a good alternative to flour.